Phosphoproteomic analysis on ovarian follicles reveals the involvement of LSD1 phosphorylation in Chicken follicle selection - Yanhong Zhang; Qiuyue Chen; Yuanyuan Guo; Li Kang; Yi Sun; Yunliang Jiang (BMC Genomics, 2023)
Abstract Background Follicle selection in chickens refers to the process of selecting one follicle from a group of small yellow follicles (SY, 6–8 mm in diameter) for development into 12–15 mm hierarchal follicles (usually F6 follicles), which is controlled by sex hormones including follicle-stimulating factor (FSH), estrogen and progesterone. Follicle selection is a critical process impacting egg production in chicken, therefore, is the focus of many studies. Phosphorylation is important for the proper function of proteins, thus, needs to be analyzed by proteomic level. Result In this study, we compared the phosphoproteomes of SY and F6 follicles in laying hens and identified 2,386 phosphoproteins and 5,940 phosphosites, of which 4,235 sites of 1,963 phosphoproteins were quantified. From SY to F6 follicles, 190 phosphorylation sites of 149 proteins changed significantly, among which the phosphorylation level of lysine demethylase 1 A (LSD1) at the conserved 54th serine (LSD1Ser54p) was significantly upregulated in F6 follicles compared to SY follicles (p < 0.05); however, the expression of chicken LSD1 were not significantly different on both mRNA and protein levels. LSD1Ser54p is mainly located in the nucleus of both SY and F6 follicles, and was higher in F6 follicles than that of SY follicles revealed by both immunofluorescence and Western blotting. LSD1Ser54p level increased after treatment with 5 ng/mL and 10 ng/mL of FSH in the theca cells and the granulosa cells of pre-hierarchal follicles, and with 50 ng/mL in granulosa cells of hierarchal follicles. In the theca cells of hierarchal follicles, estrogen stimulated the level of LSD1Ser54p in a dosage-dependent manner, and in granulosa cells of pre-hierarchal follicles, 10 ng/mL of estrogen increased LSD1Ser54p expression. Treatment with 50 ng/mL of progesterone increased LSD1Ser54p expression in theca cells of pre-hierarchal follicles, and with 10 to 100 ng/ml enhanced LSD1Ser54p expression in the granulosa cells of hierarchal follicles. Conclusion The expression dynamics of LSD1Ser54p in follicles from SY to F6 and its regulation by sex hormones suggest that it is involved in chicken follicle selection.